CONTRIBUTION OF PANDAN BEACH OBJECT TO COASTAL COMMUNITY INCOME, KELURAHAN PANDAN, CENTRAL TAPANULI DISTRICT, SUMATERA UTARA PROVINCE - Boy Rinsen Gultom; Trisla Warningsih; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTPandan Beach is one of the tourist attractions in Central Tapanuli Regency that is interesting to visit. Pantai Pandan is located in Pandan Sub-District, Pandan District, Central Tapanuli Regency. The existence of Pandan Beach has a positive impact on the coastal communities of Pandan. The existence of this tourist attraction will indirectly affect the surrounding population of economic growth, because these tourist attractions will open employment opportunities for people around the tourist attractions so that it can be said that Pandan Beach tourism object has a role for the surrounding community.The purpose of this study was to determine the contribution of Pandan Beach tourism objects to the income of coastal communities in Pandan.This research was conducted in March 2019 at Pandan Beach.This research was conducted by survey method. The data taken is primary and secondary data. Primary dataobtained through questionnaires while secondary data is in the form of data from related institutions. The analysis was carried out in a qualitative and quantitative descriptive way through the presentation of tables. The results of the analysis showed that the existence of Pantai Pandan Tourism object has a positive impact on the surrounding community where the contribution of tourism objects to community income reaches 30%.Keywords: Role, Pandan Beach, income